Comparison of scoliosis posture athlete’s table tennis and tennis at children and adolescents - Purnama, Muhammad Satria; Doewes, Muchsin; Purnama, Sapta Kunta (Journal of Education, Health and Sport, 2018)
Body posture is very important because it is closely related to health and ergonomics. When exercising, especially on the body's musculoskeletal system there will be physiological responses and adaptations during and after exercise. Table tennis and tennis are included in racquet sports which have the characteristic of using an arm to punch a racquet on the ball. The use of one side of the arm has been known to cause the possibility of scoliosis posture due to one-sided muscle imbalance. At the age of children and adolescents the body is experiencing rapid growth and development and is very easily affected. To find out how far the influence of table tennis and tennis sports forms athletic scoliosis posture and comparisons between table tennis athletes and tennis. The research method used is a comparative causal research approach. The sample in this study were samples that had met the criteria of independent variables totaling 23 people with 16 table tennis athletes at MM Shiamiq Club Manahan and 7 tennis athletes at Yunior Tennis Club Manahan. In this study, the examination of the possibility of scoliosis was assessed by measuring aspects such as leg length discrepancy, plumb line test, scapular winging test, and angle of trunk rotation. Hypothesis testing was carried out using the T-Test technique, which previously carried out normality and homogeneity tests on the sample data. The normality test is done by Ryan-Joiner (similar to Shapiro-Wilk) technique and homogeneity test is done using Levene’s Statistic technique with the help of a computer through the Minitab 17 software. From the results of the examination and measurement, Leg Length Discrepancy was obtained in the table tennis sport, were 0.887 ± 0.506 (Mean ± SD) and tennis 1,000 ± 0.493 (Mean ± SD). Plumb line test results on table tennis were 0.600 ± 0.477 (Mean ± SD) and tennis were 0.857 ± 0.556 (Mean ± SD). The results of the angle of trunk rotation in the table tennis sport were 2.813 ± 1.109 (Mean ± SD) and tennis 2.714 ± 0.756 (Mean ± SD). From the results of scapular winging test obtained (100%) the whole sample was identified as having winging scapula. From the results of the T-test analysis, Leg Length Discrepancy data obtained P-Value value of 0.626. From the results of the T-test analysis, the Plumb Line Test data obtained P-Value value of 0.270. From the results of the T-test analysis, Angle of Trunk Rotation data obtained P-Value value of 0.834. Table tennis and tennis are likely to cause scoliosis posture. There is no significant difference between scoliosis posture between athlete’s table tennis and tennis.